Innovative Approaches to Avoid Antibiotic Use in Equine Semen Cryopreservation: Advancing Sustainable Reproductive Technologies - Sonsoles Mercedes Zabala; Consuelo Serres; Natalia Montero; Francisco Crespo; Pedro Luis Lorenzo; Verónica Pérez-Aguilera; Agustín Oliet; Virginia Hijón; Santiago Moreno; Bruno González-Zorn; Luna Gutiérrez-Cepeda (Animals)
This study evaluated the impact of different processing techniques on microbial load and sperm quality in frozen–thawed equine semen to identify alternatives to reduce the preventive use of antibiotics. Semen was obtained and processed under rigorous hygiene measures from ten stallions, using four protocols: Simple Centrifugation with antibiotics (S+) and Simple Centrifugation (S−), Filtration (F−) and Single-Layer Colloidal Centrifugation (C−) in an antibiotic-free extender. Microbial load in different culture media, sperm viability and motility were assessed. Microbial load results were consistent across protocols, except in Columbia 5% Sheep Blood Agar media, where S− exhibited higher microbial load than S+ (p < 0.05). However, F− and C− showed similar microbial loads to S+. No significant differences were observed in progressive motility, average path velocity, straight-line velocity or wobble parameters between protocols. Total motility and viability were significantly higher in S+ compared to other treatments (p < 0.05). Thus, regardless of antibiotics, the proposed methods achieved results similar to the traditional antibiotic-inclusive protocol in terms of microbial load and the most relevant semen quality parameters. These findings suggest that the use of F− and C−, combined with optimized hygiene measures, offers an effective alternative to reduce the prophylactic use of antibiotics in semen extenders.